BALOCHI A DISAPPEARING LANGUAGE IN PUNJAB PROVINCE OF PAKISTAN - Baloch, Dr. Ghulam Qasim Mujahid (Hanken, 2015)
The Balochi is an old language of Pakistan, mostly spoken in Balochistan, Sindh and Punjab provinces of the country. But it is rapidly disappearing from face of Punjab province as it has got no opportunity of being medium of instruction in educational institutions and no Balochi Department could be opened in any university of the province. If a language is lost its whole literature, culture and past history is lost which is a great loss of knowledge for mankind. Due to other language's pressure the new Baloch generation avoids speaking Balochi and usually speaks more spoken other languages. Many words of: English, Urdu, Punjabi and Jatki (Saraiki) languages are being mixed in Balochi language so it is losing its classical form and beauty in the provice. Balochi Language which completely disappeared from North West Frontier Province (Khyber Pakhtoon Khawh) of Pakistan; is rapidly going to face the same fate in the Punjab Province of Pakistan.